Industrial and organisational psychology (Cambridge)
Industrial and Organizational Psychology focuses on interactive exchanges on topics of importance to science and practice in our field.The journal features focal articles which present new ideas or different takes on existing ideas that stimulate conversation on an important issue for the field (or potentially a pair of papers taking opposite sides in a debate).
Keywords: Psychology